Pharmacodynamics, pharmacokinetics, interactions with other drugs, toxicity and clinical effectiveness of proton pump inhibitors - Łukasz Wołowiec; Joanna Osiak-Gwiazdowska; Albert Jaśniak; Michał Janiak; Lidia Wydeheft; Magdalena Łukasiak; Małgorzata Pellowska; Grzegorz Grześk (Frontiers in Pharmacology)
The document comprehensively reviews proton pump inhibitors (PPIs), focusing on their pharmacodynamics, pharmacokinetics, drug interactions, toxicity, and clinical efficacy. PPIs irreversibly inhibit the H+/K+-ATPase enzyme in gastric parietal cells, effectively reducing gastric acid secretion. These drugs are widely prescribed for conditions like gastroesophageal reflux disease (GERD), peptic ulcer disease, eradication of Helicobacter pylori and as a prevention against bleeding from gastrointestinal tract. The review article highlights significant drug interactions associated with PPIs. Omeprazole, for instance, can interfere with the metabolism of clopidogrel, reducing its antiplatelet efficacy, which may have clinical implications. The article also discusses other drug interactions, including anticoagulants (e.g., warfarin), selective serotonin reuptake inhibitors (SSRIs), and immunosuppressive and chemotherapeutic drugs, as well as the side effects associated with taking PPIs. Long-term use of PPIs is linked to plenty of adverse effects, such as vitamin B12 and calcium deficiencies, which can lead to bone fractures. An increased risk of infections, including Clostridium difficile and small intestinal bacterial overgrowth (SIBO), is also noted. Cardiovascular risks, such as myocardial infarction and stroke, are observed in some patients on high-dose or prolonged PPI therapy. In rare cases, nephrotoxicity and hepatotoxicity are reported. Additionally, the document examines the potential role of PPIs in exacerbating certain cancers, such as gastric adenocarcinoma, and in influencing the severity of COVID-19 symptoms. PPIs are proven effective in treating GERD and preventing complications from nonsteroidal anti-inflammatory drugs (NSAIDs), particularly in reducing the risk of NSAID-induced ulcers. The document stresses the importance of understanding drug interactions and the need for individualized treatment to minimize adverse effects. Ongoing research into PPIs’ long-term safety and efficacy remains essential, particularly given their widespread use in clinical practice.